Renal Fibrosis in Murine Obstructive Nephropathy Is Attenuated by Depletion of Monocyte Lineage, Not Dendritic Cells - Yuichi Machida; Koichiro Kitamoto; Yasukatsu Izumi; Masayuki Shiota; Junji Uchida; Yukimi Kira; Tatsuya Nakatani; Katsuyuki Miura (Elsevier, 2010)
Abstract.: The role of renal dendritic cells (DCs) in renal fibrosis is unknown. The present study was conducted to examine the relative role of renal DCs and macrophages in the development of renal fibrosis in murine obstructive nephropathy. CD11c-diphtheria toxin receptor (DTR) transgenic mice and CD11b-DTR transgenic mice were subjected to unilateral ureteral obstruction. To conditionally and selectively deplete DCs or macrophages, DT was given to these mice and kidneys were harvested on day 5. Ureteral obstruction elicited renal fibrosis characterized by tubulointerstitial collagen III deposition and accumulation of α-smooth muscle actin-positive cells. Flow cytometric analysis revealed a marked increase in cell counts of F4/80+ macrophages, F4/80+ DCs, as well as neutrophils and T cells in the obstructed kidney. DT administration to CD11c-DTR mice led to selective depletion of renal CD11c+ DCs, but did not affect renal fibrosis. In contrast, administration of DT to CD11b-DTR mice resulted in ablation of all monocyte lineages including macrophages and DCs and attenuated renal fibrosis. Our results do not support the role of renal DCs, but confirm the importance of monocyte lineage cells other than DCs in the development of the early phase of renal fibrosis following ureteral obstruction in mice. Keywords:: renal fibrosis, inflammation, monocyte, macrophage, dendritic cell